Liechtenstein : Detailed Assessment Report on Anti-Money Laundering and Combating the Financing of Terrorism. (IMF Staff Country Reports; Country Report ;, 2008)
Liechtenstein's financial sector business has created money laundering risks. The investigative powers of the law enforcement authorities are comprehensive enough to enable them to conduct serious investigations in an effective way. Money laundering is criminalized broadly in line with the international standard. Liechtenstein relies on its trust service providers to obtain, verify, and retain records of the beneficial ownership and control of legal persons. Liechtenstein should conduct a full review of its laws concerning non-profit organizations to assess their adequacy for combating the financing of terrorism.